KEPASTIAN HUKUM PENGATURAN ASET KRIPTO DI INDONESIA DAN IMPLIKASINYA TERHADAP PERLINDUNGAN KONSUMEN - Azhari Dzulqarnain; Aris Machmud (Jurnal Ilmiah Advokasi, 2026)
The rapid development of crypto assets in Indonesia has created significant legal challenges, particularly regarding legal certainty and consumer protection. Although crypto assets have been recognized as tradable commodities and are currently undergoing regulatory transition into the financial sector, the coexistence of multiple regulatory regimes has generated uncertainty concerning their legal status, institutional authority, and mechanisms for consumer protection. This study aims to analyze the legal framework governing crypto assets in Indonesia following the enactment of Law Number 4 of 2023 on Financial Sector Development and Strengthening (P2SK Law) and Government Regulation Number 49 of 2024, as well as to examine the adequacy of legal protection available to crypto-asset consumers. This research employs a normative legal research method using statutory, conceptual, and comparative approaches based on primary, secondary, and tertiary legal materials. The findings reveal that although Indonesia has established a more structured regulatory framework through the transfer of supervisory authority from Bappebti to the Financial Services Authority (OJK), the legal framework remains fragmented, resulting in overlapping institutional authority, uncertainty in dispute resolution mechanisms, and limited legal remedies for consumers. The study further demonstrates that existing regulations have not comprehensively integrated consumer protection principles, particularly regarding compensation mechanisms, platform accountability, and legal certainty for digital asset ownership. This research contributes by proposing an integrated regulatory model that harmonizes financial regulation, consumer protection law, and digital asset governance to strengthen legal certainty and enhance consumer protection within Indonesia's crypto-asset ecosystem.Keywords: Crypto Assets; Legal Certainty; Consumer Protection; Digital Financial Assets; Financial Regulation